Outer Membrane Vesicle Production Facilitates LPS Remodeling and Outer Membrane Maintenance in Salmonella during Environmental Transitions - Katherine E. Bonnington (American Society for Microbiology, 2016)
ABSTRACT The ability of Gram-negative bacteria to carefully modulate outer membrane (OM) composition is essential to their survival. However, the asymmetric and heterogeneous structure of the Gram-negative OM poses unique challenges to the cell’s successful adaption to rapid environmental transitions. Although mechanisms to recycle and degrade OM phospholipid material exist, there is no known mechanism by which to remove unfavorable lipopolysaccharide (LPS) glycoforms, except slow dilution through cell growth. As all Gram-negative bacteria constitutively shed OM vesicles (OMVs), we propose that cells may utilize OMV formation as a way to selectively remove environmentally disadvantageous LPS species. We examined the native kinetics of OM composition during physiologically relevant environmental changes in Salmonella enterica, a well-characterized model system for activation of PhoP/Q and PmrA/B two-component systems (TCSs). In response to acidic pH, toxic metals, antimicrobial peptides, and lack of divalent cations, these TCSs modify the LPS lipid A and core, lengthen the O antigen, and upregulate specific OM proteins. An environmental change to PhoP/Q- and PmrA/B-activating conditions simultaneously induced the addition of modified species of LPS to the OM, downregulation of previously dominant species of LPS, greater OMV production, and increased OMV diameter. Comparison of the relative abundance of lipid A species present in the OM and the newly budded OMVs following two sets of rapid environmental shifts revealed the retention of lipid A species with modified phosphate moieties in the OM concomitant with the selective loss of palmitoylated species via vesiculation following exposure to moderately acidic environmental conditions. IMPORTANCE All Gram-negative bacteria alter the structural composition of LPS present in their OM in response to various environmental stimuli. We developed a system to track the native dynamics of lipid A change in Salmonella enterica serovar Typhimurium following an environmental shift to PhoP/Q- and PmrA/B-inducing conditions. We show that growth conditions influence OMV production, size, and lipid A content. We further demonstrate that the lipid A content of OMVs does not fit a stochastic model of content selection, revealing the significant retention of lipid A species containing covalent modifications that mask their 1- and 4′-phosphate moieties under host-like conditions. Furthermore, palmitoylation of the lipid A to form hepta-acylated species substantially increases the likelihood of its incorporation into OMVs. These results highlight a role for the OMV response in OM remodeling and maintenance processes in Gram-negative bacteria.